Homeland Security Organization in Defence Against Terrorism - Charvat, J.P.I.A.G (IOS Press, 2014)
The Centre of Excellence – Defence against Terrorism (COE-DAT) hosted an Advanced Research Workshop entitled "Homeland Security Organization in Defence Against Terrorism" that was conducted in Ankara from 19-20 November 2009. The workshop consisted of five sessions, with at least two experts in their field presenting information pertinent to the session topic, followed by a debate period on that topic. A total of thirteen experts from eight countries helped the forty participants from thirteen countries discuss these issues in order to facilitate awareness in NATO and affiliated countries. The articles in this book reflect those presentations and discussions.